Challenges in managing complex chronic middle ear disease: MERF experience - Natarajan, Kiran; Devaraju S., Aruna; Shrivastava, Anubhav; Ramasamy, Swathi; Sampathkumar, Raghunandhan; Kameswaran, Mohan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Chronic otitis media is one of the commonest conditions managed in otolaryngology practice. In developing countries such as India, advanced disease presentation is often seen mostly owing to lack of awareness of the disease and its potential complications, long distance between the patient’s home and the treatment centre, causing delay in treatment. Surgical management is the mainstay of treatment of chronic otitis media. Methods: The aim of this study was to retrospectively analyze the patients with complex chronic middle ear disease, who underwent tympanomastoid surgery. Forty-seven patients (4.9%) out of a total of 968 patients with chronic otitis media presented with complex advanced disease and challenging intra-operative situations at our tertiary referral centre between January 2016 to December 2020. The extent of disease, associated complications, challenges in surgical management, and the eventual outcomes were studied in detail. Results: Among these forty-seven patients, there were 24 males and 23 females. Of the 47 patients, 8 were children (17%). Extensive cholesteatoma causing facial palsy, labyrinthine fistula, dural involvement, internal auditory meatus involvement, extensive granulations extending into the inner ear through the oval or round window, extensive tympanosclerosis was noted in these patients. All patients underwent surgical management, and achieved satisfactory outcomes. Conclusions: Advanced chronic otitis media has the potential to pose various challenges during tympanomastoid surgery. Appropriate planning for surgery aiming at complete disease clearance, meticulous after-care and long-term surveillance result in favorable outcomes.